An Updated Overview of Risk Factors for Shoulder Stiffness - van Hattem, Suncana; Regener, Eva-Maria; Prangenberg, Christian; Strauss, Andreas Christian; de Girolamo, Laura; Burger, Christof; Wirtz, Dieter Christian; Cucchi, Davide (Zeitschrift für Orthopädie und Unfallchirurgie, 2024)
A painful reduction in shoulder mobility, known as “shoulder stiffness”, can occur both as a primary idiopathic condition and as a secondary condition, for example, following surgical procedures. Various factors can contribute to the development of primary shoulder stiffness. In this review we summarize the pathophysiological mechanisms, genetic influences, endocrine disorders, metabolic conditions, as well as other diseases and medical-therapeutic approaches that might have an impact on the development of primary shoulder stiffness.
Keywords: shoulder stiffness; frozen shoulder; adhesive capsulitis; inflammation; risk factors